Filling the leadership pipeline - Kaiser, Robert B. (Center for Creative Leadership, 2005)
Competition is fiercer today than ever before, and effective leadership represents a rare source of competitive advantage. With strong leadership and a richly stocked pool of future leaders, organizations prosper and endure. There is an easy case to make for the imperative of investing in tomorrow's leaders today. It's the law of supply and demand: more organizations in greater competition under increased pressure to perform put a premium on scarce talent. The labor economy has become a seller's market, and poaching or luring talent away from other organizations is a losing proposition. The alternative is to become good at developing your talented managers into great leaders and aggressively seeking out potential and developing it anywhere and everywhere you can find it across the organization. The purpose of this volume is to share what has been learned in the last few years of increased attention to the systematic and strategic cultivation of leadership talent. The time is ripe for leading practitioners to share key lessons about building and filling a leadership pipeline.